Keith Muckelroy: Methods, Ideas and Maritime Archaeology - Harpster, Matthew (Springer, 2009)
Between his graduation from the Department of Archaeology at Cambridge University in 1974 and his death in 1980, Keith Muckelroy's work and ideology were crucial in promoting an alternative research methodology in maritime archaeology. Instead of a particularist or historiographic approach, methods prominent both then and now, Muckelroy's methodology was grounded in the foundations of the prehistoric archaeology he learned under Grahame Clark and David Clarke at Cambridge, and the basic tenets of New Archaeology maturing in the United States during the 1970s. This paper, which elucidates Muckelroy's methods and research, is neither a complete biography nor an exhaustive study of his ideas. Although unpublished letters, papers and notes were studied in archives at Cambridge University and the National Maritime Museum, there is still much more to be learned from many of his former colleagues and their memories-only a handful of those individuals were consulted during the creation of this work. Nevertheless, this paper was written in the hope that by understanding Muckelroy's ideas, and placing them in the larger framework of the discipline of archaeology, maritime archaeologists who are attempting to pursue a variety of approaches may find inspirations, models and, perhaps, questions that still need to be answered.
Keywords: Muckelroy; Maritime archaeology; Statistical analysis; The New Archaeology; CUUEG